Napoléon et l’Espagne - Natalie Petiteau (Mélanges de la Casa de Velázquez, 2008)
We know how Napoleon viewed the war in Spain as a «fatal knot», but historians have frequently neglected to analyse the ways in which that knot came to be tied. Rereading the sources, including official ones, one can grasp his ambition to be sure, but he seems also to have had a relatively clear idea as to the difficulties that had to be faced. At the same time, the accounts of contemporary witnesses reveal the extent to which engagement in this conflict was seen as the Empire’s turning-point, as historians were quick to confirm in exactly the same terms.